2020
DOI: 10.1007/s10010-020-00399-x
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung und Optimierung des Einflusses von niedrig auflösenden Rotorlagegebern auf die Fahrbarkeitsfunktionen elektrifizierter Fahrzeugantriebssysteme mittels eines Hardware-in-the-Loop-Prüfstands

Abstract: Zusammenfassung Elektrofahrzeuge unterscheiden sich bezüglich ihres Antriebsstrangs deutlich von Kraftfahrzeugen mit verbrennungsmotorischem Antrieb. Typischerweise ist keine Trennkupplung verbaut und mit einer geringen Anzahl von Gangstufen reduzieren sich die Reibung und die Dämpfung. Ein Hauptproblem hierbei ist die Schwingungsentwicklung durch innere (Drehmomentänderungen der Elektromaschine, Bremseingriffe) und äußere Anregung (Fahrbahnunebenheiten, Schlaglöcher usw.). Um entstehende Schwingungen im Antri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…These systems are distinguished either as monolithic (single DUT) or distributed (multiple DUTs) [27, p. 78]. A requirement specification for fast communication between all corresponding interfaces leads to a change in data exchange from Ethernet (user datagram protocol or UDP) to EtherCAT or direct (analogue) linkage of components (see examples [51,65,66,96]).…”
Section: A a Summary Of X-in-the-loop Approaches To Datementioning
confidence: 99%
“…These systems are distinguished either as monolithic (single DUT) or distributed (multiple DUTs) [27, p. 78]. A requirement specification for fast communication between all corresponding interfaces leads to a change in data exchange from Ethernet (user datagram protocol or UDP) to EtherCAT or direct (analogue) linkage of components (see examples [51,65,66,96]).…”
Section: A a Summary Of X-in-the-loop Approaches To Datementioning
confidence: 99%
“…The test bench load machine applies the resulting torque, calculated from the simulation of the vehicle wheel with the tire-road contact and the driving resistance forces from the vehicle longitudinal dynamics (gradient, rolling, and air resistance forces), against the test bench drive machine. A suitable HiL simulation model is used for this purpose, which is described in detail in [15,16]. The reacting torques are determined by the HiL simulation model and the angular velocity at the vehicle wheel hub is reproduced by the test bench load machine.…”
Section: Test Environmentmentioning
confidence: 99%
“…Furthermore, automotive-typical sensors such as ABS speed sensors are integrated. In [15,16,20] is demonstrated that the natural frequency of the HiL test bench together with the HiL simulation model is approximately 8 Hz and the oscillation behavior corresponds to a real electrified vehicle drive system.…”
Section: Test Environmentmentioning
confidence: 99%
See 2 more Smart Citations